Information Technology Implementation within the Bogor Regency Office for Regional Revenue and Asset Management (Open Society Conference, 2023)
The era of digital-based governance is no longer merely a directive but has evolved into an imperative that demands implementation. Best practices in e-government within a specific region ought to be disseminated to the general public to facilitate their adoption in other contexts. Likewise, the commendable practices observed within the Bogor Regency Office for Regional Revenue and Asset Management (Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Bogor or BPKAD), which has consistently achieved Unqualified Opinion (Wajar Tanpa Pengecualian or WTP) for six consecutive periods owing to the utilization of the Information Technology Application for Local Government Asset Cycle (Aplikasi Teknologi Informasi Siklus Barang Daerah or ATISISBADA), warrant broader recognition. Employing a quantitative research methodology and total sampling techniques, this study analyzes the aforementioned practices across various dimensions of performance, including hardware functionality, software quality, procedural protocols, network infrastructure, and user competencies. Optimal performance across these five dimensions is achieved through the seamless integration of robust hardware infrastructure, deployed ubiquitously across the computing environment of the Bogor Regency Office for Regional Revenue and Asset Management. Furthermore, this application is fortified by auxiliary software quality in the form of the Regional Financial Management Information System (Sistem Informasi Pengelolaan Keuangan Daerah or SIPKD), albeit now deprecated. The enhancement of user competencies through effective socialization initiatives has notably contributed to the elevated quality of financial reporting and asset management within the aforementioned office. These circumstances, in turn, exert a tangible influence on the transparency of financial matters as perceived by the public.